2012
DOI: 10.1590/s1806-66902012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties of an oxisol under organic management as influenced by application of sugarcane bagasse ash

Abstract: -There are large areas of Oxisols in South America, including Brazil, with low fertility and acidity. To improve crop yields on these Oxisols, liming and fertilization is an essential practice. However, besides the high cost of fertilizers, chemical fertilizers cannot be used in organic production systems, except insoluble sources. Ash is one of the alternative source of supplying macro and micronutrients. A field experiment was conducted, in a completely randomized block design in a factorial arrangement (thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
2
22
0
3
Order By: Relevance
“…Wood ash oxides, hydroxides and carbonates of Ca and Mg and basic cation significant amounts, such as calcium, magnesium and potassium reduce soil acidity and increase soil pH, improving its fertility (Haraldsen et al, 2011;Norstrom et al, 2012). Similar effect to that of the present study was observed by Ferreira et al (2012) when wood ash was used as fertilizer in Latossol. In fact, these authors find that soil content of H + Al significantly decreased with wood ash rate increase.…”
Section: Resultssupporting
confidence: 86%
“…Wood ash oxides, hydroxides and carbonates of Ca and Mg and basic cation significant amounts, such as calcium, magnesium and potassium reduce soil acidity and increase soil pH, improving its fertility (Haraldsen et al, 2011;Norstrom et al, 2012). Similar effect to that of the present study was observed by Ferreira et al (2012) when wood ash was used as fertilizer in Latossol. In fact, these authors find that soil content of H + Al significantly decreased with wood ash rate increase.…”
Section: Resultssupporting
confidence: 86%
“…Application of plant ash has been the subject of many studies showing an increase in the amount of K in tropical soils (Augusto et al, 2008;Ferreira et al, 2012). The high content of K in AR (36, 6 mmolc dm -3 in this study) can be justified by the high content of this macronutrient in sugar cane.…”
Section: ) -----------% -------------------(Mg Dm -3 ) --------mentioning
confidence: 60%
“…This undesired attributes affect in a negative form the soil quality and consequently the development of vegetation. Ferreira et al (2012) pointed that a reduction of acidity after ash application facilitates plant growth. This material contains high amounts of alkaline substances which reduces the potential acidity.…”
Section: Resultsmentioning
confidence: 99%
“…As an organic residue, macrophytes collected in lakes and rivers have been recommended, for having biomass rich in macro and micronutrients, which positively influence soil physical, chemical and biological properties (Sampaio & Oliveira, 2005). Another residue, the ash from the burning of sugarcane bagasse, is also a source of macro and micronutrients, retains humidity and can partially correct soil acidity (Ferreira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%